BOOST QUASI-RESONANT CONVERTERS FOR PHOTOVOLTAIC SYSTEM - Harasimczuk, Michał (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
This paper presents PWM quasi-resonant boost converter for photovoltaic systems. The use of a resonant circuit enabled switching transistor in zero current (ZCS). Continuous conduction mode (CCM) with current control has been achieved. This allows to implement MPPT algorithm. The use of transistor switching resonant capacity allowed source (PV) current ripple with constant frequency and high efficiency in different load current. In the article has been discussed principle of operation the converter. Simulation converter in PSpice have been presented.